Fill in the missing fractions to create a true equation.(1 point)

___ /5 − 12 = 3/___

1 answer

To solve the equation, we start from:

\[ \frac{x}{5} - 12 = \frac{3}{y} \]

First, add 12 to both sides to isolate the fraction:

\[ \frac{x}{5} = \frac{3}{y} + 12 \]

Now, let's express 12 as a fraction with a denominator of \(y\):

\[ 12 = \frac{12y}{y} \]

Thus, we can rewrite the right side:

\[ \frac{x}{5} = \frac{3 + 12y}{y} \]

Next, we cross-multiply to eliminate the fractions:

\[ x \cdot y = 5(3 + 12y) \]

Distributing the 5:

\[ xy = 15 + 60y \]

Now we can rearrange this equation to isolate \(x\):

\[ xy - 60y = 15 \]

Factoring out \(y\):

\[ y(x - 60) = 15 \]

From here, we can find specific values for \(x\) and \(y\). Let's say:

  1. Let \(y = 1\):

    • \(1(x - 60) = 15\) → \(x - 60 = 15\) → \(x = 75\) So, one pair is \( (75, 1) \).
  2. Let \(y = 3\):

    • \(3(x - 60) = 15\) → \(x - 60 = 5\) → \(x = 65\) So, another pair is \( (65, 3) \).
  3. Let \(y = 5\):

    • \(5(x - 60) = 15\) → \(x - 60 = 3\) → \(x = 63\). So, another pair is \( (63, 5) \).

Based on the pairs provided, we could replace the missing fractions in our original equation like this:

Thus, we can conclude:

\[ 75/5 - 12 = 3/1 \]

or

\[ 65/5 - 12 = 3/3 \]

or

\[ 63/5 - 12 = 3/5 \]

All satisfy the equation, and thus the missing fractions could be represented as:

Final Answer:

75/5 - 12 = 3/1 (which is a valid option).

Any of the pairs will work.

Similar Questions
  1. QuestionFill in the missing fractions to create a true equation.(1 point)  /5 − 12 =  3/
    1. answers icon 1 answer
    1. answers icon 10 answers
    1. answers icon 1 answer
    1. answers icon 3 answers
more similar questions